Faecal unconjugated bile acids in patients with colorectal cancer or polyps. Issue 9 (September 1992) - Imray, C H; Radley, S; Davis, A; Barker, G; Hendrickse, C W; Donovan, I A; Lawson, A M; Baker, P R; Neoptolemos, J P
Abstract : The unconjugated faecal bile acid profiles of 14 patients with colorectal cancer, nine patients with polyps and 10 controls were compared using gas liquid chromatography, controlling for such confounding variables as cholecystectomy, gall stones and hepatic function. Patients with adenomatous polyps had a higher concentration of faecal bile acids (5.23 mumol/g, 2.16-13.67 (median, range) v 1.96, 0.91-6.97; p = 0.016) lithocholic acid (2.41, 0.88-3.22 v 1.07, 0.38-2.03; p = 0.013) and total secondary bile acids (5.23, 2.16-13.4 v 1.96, 0.73-6.63; p = 0.02) compared with control subjects. Patients with colorectal cancer had an increased (p = 0.029) proportion of secondary faecal bile acids (mol%) compared with controls (100, 96.5-100 v 95.19, 81.73-100) and the ratios of the primary bile acids, cholic and chenodeoxycholic acid, to their respective derivatives (secondary bile acids) were significantly lower in cancer patients compared with control and patients with polyps (p = 0.034 to 0.004). This study lends further support to the theory that bile acids may play a role in the development of polyps and colorectal cancer.